Climate services for protection against wheat blast in Bangladesh - CGIAR Research Program on Wheat (2019)
This Wheat Blast Early Warning System can be used by farmers to protect their wheat crops from wheat blast. This system has been completed and is reaching >850 extension agents regularly with updated blast advisories. The system has been adopted and endorsed by Bangladesh's Department of Agricultural Extension, Meteorological Department, and Bangladesh Wheat and Maize Research Institute.